Praktik Green HRM dalam Mengejar Lingkungan Bisnis Berkelanjutan - Zurfiera Dianal Fianti; Muammar khadafi (Yayasan Tri Edukasi Ilmiah, 2024)
Environmental sustainability is causing increasing concern among business executives, governments, consumers, and management experts. In the midst of the struggles of stakeholders and the challenges and opportunities of environmental problems, the HRM function participates in ongoing discussions and debates. The business domain sees the origins of Green HRM with the expanding role of HRM functions in realizing environmentally friendly businesses. This research aims to explain the concept of Environmentally Friendly Human Resource Management, the company's approach to environmentally friendly HRM, its advantages, policies and practices. This paper discusses the current trends of eco-friendly HRM practices in companies based on findings from several studies, survey reports and secondary data from corporate web resources. This also shows the role of the Human Resources function in creating a 'green' culture in the company